2016
DOI: 10.7554/elife.20697
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized excitability in a network enables generation of internal neuronal sequences

Abstract: Hippocampal place field sequences are supported by sensory cues and network internal mechanisms. In contrast, sharp-wave (SPW) sequences, theta sequences, and episode field sequences are internally generated. The relationship of these sequences to memory is unclear. SPW sequences have been shown to support learning and have been assumed to also support episodic memory. Conversely, we demonstrate these SPW sequences were present in trained rats even after episodic memory was impaired and after other internal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 67 publications
(131 reference statements)
3
17
0
Order By: Relevance
“…This finding parallels previous reports of sequence reactivation in hippocampal neurons representing spatial trajectories, but for the temporal domain (Diba & Buzsáki, 2007;Foster & Wilson, 2006). Although a recent report has shown that the formation of place and time cell sequences differs (Wang, Roth, & Pastalkova, 2016), the reactivation of temporal and spatial sequence during sharp-wave ripples depends on similar mechanisms. In addition, our results suggest that the occurrence of reactivations containing only time cells supports the independent processing of temporal experiences in blocks of selective reactivation events (Gupta, van der Meer, Touretzky, & Redish, 2012).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This finding parallels previous reports of sequence reactivation in hippocampal neurons representing spatial trajectories, but for the temporal domain (Diba & Buzsáki, 2007;Foster & Wilson, 2006). Although a recent report has shown that the formation of place and time cell sequences differs (Wang, Roth, & Pastalkova, 2016), the reactivation of temporal and spatial sequence during sharp-wave ripples depends on similar mechanisms. In addition, our results suggest that the occurrence of reactivations containing only time cells supports the independent processing of temporal experiences in blocks of selective reactivation events (Gupta, van der Meer, Touretzky, & Redish, 2012).…”
supporting
confidence: 89%
“…S5). Similar to previous reports (Lee & Wilson, 2002;Wang, Roth, & Pastalkova, 2016), the reactivation of time cell sequences were temporally compressed, lasting around 200 ms (see Supporting Information Fig. S6).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This suggests that the theta rhythm, a striking pattern of brain activity in its own right (Buzsaki, ; Buzsaki, ; Buzsáki, ; Green & Arduini, ; Hasselmo, ), might be a marker of the hippocampal state in which place firing occurs. Indeed, numerous results suggest that the theta rhythm has a functional role in the hippocampus (Ranck Jr, ; Winson, ; Buzsaki et al, ; O'Keefe & Recce, ; O'Keefe, ; Wang, Romani, Lustig, Leonardo, & Pastalkova, ; Redish, ; Wang, Roth, & Pastalkova, ; also see Brandon, Koenig, Leutgeb, & Leutgeb, ).…”
Section: Three Brain States In the Hippocampusmentioning
confidence: 99%
“…There are two reasons why neural swarming control must decouple each agent's physical location from its internal selflocalization. First, the multiplicity of agents is a qualitative difference with brain circuits; every hippocampal neuron in a biological network corresponds to the same single agent (e.g., a rat) and has particular inputs from internal processing or sensory inputs (Wang et al, 2016) that contribute to the appearance and location of the cell's place field. Given the analogy of agents to neurons ( Fig.…”
Section: Hippocampal Model Mechanismsmentioning
confidence: 99%